2014
DOI: 10.1159/000365353
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Myelomeningocele Repair: The Post-MOMS Experience at the Children's Hospital of Philadelphia

Abstract: Background: Fetal myelomeningocele (fMMC) repair has become accepted as a standard of care option in selected circumstances. We reviewed our outcomes for fMMC repair from referral and evaluation through surgery, delivery and neonatal discharge. Material and Methods: All patients referred for potential fMMC repair were reviewed from January 1, 2011 through March 7, 2014. Maternal and neonatal data were collected on the 100 patients who underwent surgery. Results: 29% of those evaluated met the criteria and unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
164
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 180 publications
(186 citation statements)
references
References 14 publications
10
164
2
1
Order By: Relevance
“…We concentrated on the comparison of our data (39 cases with neonatal results) with data from the postMOMs experience, which focused on the perinatal results rather than on a longer-term follow-up of the infants [13] . Our inclusion criteria for fetal MMC repair were comparable, as were most of the maternal and fetal characteristics at the time of fetal surgery, which are summarized as follows (present series × post-MOMs experience): average GA at surgery (24.5 × 23.3 weeks); most frequent upper level of the MMC (L1-L4: 74.2 × 87.0%); average size of the larger lateral cerebral ventricle (11.3 × 10.6 mm), and presence of talipes (38.5 × 15.0%).…”
Section: Discussionmentioning
confidence: 99%
“…We concentrated on the comparison of our data (39 cases with neonatal results) with data from the postMOMs experience, which focused on the perinatal results rather than on a longer-term follow-up of the infants [13] . Our inclusion criteria for fetal MMC repair were comparable, as were most of the maternal and fetal characteristics at the time of fetal surgery, which are summarized as follows (present series × post-MOMs experience): average GA at surgery (24.5 × 23.3 weeks); most frequent upper level of the MMC (L1-L4: 74.2 × 87.0%); average size of the larger lateral cerebral ventricle (11.3 × 10.6 mm), and presence of talipes (38.5 × 15.0%).…”
Section: Discussionmentioning
confidence: 99%
“…Europe and Asia had more high-volume centers, whereas South America, the Middle East, and Australia had mainly low-volume centers [59] . A recent post-MOMS publication has shown that only 29% of referrals are actually eligible [60] . It has not been universally agreed if ex utero intrapartum treatment deliveries count toward this minimum annual volume requirement.…”
Section: Personnelmentioning
confidence: 99%
“…1 Although it is hoped that an evidence-based approach to medical decisions using the MOMS results would improve the quality of information received by pregnant patients, we believe that unless specific steps are taken, prenatal counseling for myelomeningocele (counseling that occurs in myriad locations across the United States) will be persistently marred by hidden biases and excess variability.…”
mentioning
confidence: 99%
“…Adding to the uncertainty, long-term outcomes are unavailable; prognosis remains difficult to predict for any given fetus; and posttrial complication rates reportedly differ from trial results, with higher rates of perinatal death (6% vs 3%) and respiratory distress syndrome (52% vs 21%) but fewer maternal complications (pulmonary edema, 2% vs 6%; maternal transfusion, 3.4% vs 9%). 1 Women undergoing intrauterine surgery require cesarean deliveries for all future pregnancies. The reasoning regarding such multifaceted risk/benefit tradeoffs for obstetric and neonatal interventions is notably difficult for both physicians and patients.…”
mentioning
confidence: 99%